Problems Faced by the Farmers in Post-harvest Management of Pomegranate in Western Rajasthan - Surliya, Vikash; Meena, Satyveer Singh (Indian Journal of Extension Education, 2024)
It attempted to analyse the problems faced by farmers in post-harvest management of pomegranates in Barmer district of Rajasthan in 2022. The association of technical problems was checked with the education level of farmers. The data were taken from 120 farmers. Garret’s ranking method was employed to rank the problems faced by the farmers. A chi-square test was employed to check the measure of association between technical problems and the education level of farmers. The results revealed the five major categories of problems (Environmental, technical, infrastructure, financial, and market related) faced by farmers in post-harvest management of pomegranates. The major technical problem was the lack of a processing industry at the village level ranked as I with a mean value 70.45. The market-related problem was the unavailability of market of fruits at the village level ranked as I with a mean value 63.50. The chi-square test results revealed that there was an association between the education level of farmers and technical problems.
Keywords: Chi-square; Farmers; Garret ranking; Post-harvest management; Problems